Purine content of hospital meals and its effect on serum uric acid, urine pH, and urinary uric acid excretion. (2nd December 2022) - Takayanagi, Fukue; Uchino, Takuya; Motoki, Natsumi; Uchida, Kanae; Asakura, Hitomi; Uno-Eder, Kiyoko; Nomura, Takahiro; Tsukamoto, Kazuhisa; Fukuuchi, Tomoko; Yamaoka, Noriko; Kaneko, Kiyoko
Abstract: Hospital meals are prepared with the nutrients required by the patient's medical condition in consideration. However, no research on the purine content of hospital meals has been conducted, and it is not shown on the purine content. The recommended purine consumption for patients with gout and hyperuricemia is 400 mg/day based on the Japanese guidelines for the management of hyperuricemia and gout. In this study, the purine content in hospital meals was evaluated using the purine content of foods previously determined by our laboratory as a reference. The serum uric acid levels and uric acid excretion in admitted patients who consumed these diets were examined.